“Facets of Beauty: Evidence-Based Guidelines for Porcelain Veneers in the Anterior Esthetic Zone” (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Porcelain veneers represent a minimally invasive yet highly aesthetic treatment option for anterior teeth. Advances in ceramic materials, adhesive protocols, and digital workflows have significantly improved longevity and predictability. This narrative review outlines the indications, contraindications, material choices, preparation designs, adhesive cementation protocols, and complication management related to veneer therapy. Particular emphasis is placed on evidence-based decision-making and clinical nuances that influence long-term success, including case selection, occlusal planning, and periodontal considerations. The review also highlights methodological limitations in the current literature—such as heterogeneous follow-up periods, variable preparation designs, and differing adhesive strategies—that may affect interpretation of survival data. Comparative insights from long-term clinical trials and systematic reviews are integrated to provide balanced, clinically relevant guidelines.